'Habitually Embodied' Memories: The Materiality and Physicality of Music in Hardy's Poetry. Issue 2 (17th August 2020) - Charlwood, Catherine
Abstract : This article reads Thomas Hardy's many musical instrument poems as the meeting point for the concerns of several critical fields: material culture, memory studies and the emerging interdisciplinary field of musical haptics. Close readings illuminate not only their relevance to such enquiries, but also how Hardy's manipulation of poetic form engenders a tactile musicality or 'poetics of touch' (as Marion Thain puts it). This article focuses on the aspects of these poems which have undergone least exploration: the depiction of the bodily effort involved in music-playing. While some of the poems are critical favourites ('Old Furniture') many of those studied here are routinely overlooked. A mnemonically-minded poet, Hardy wrote about the memories objects hold and the memories that may be mediated through them. For Hardy, the history of objects is inseparable from that of their now-dead owners: person and thing are tied together in memory. This is in part due to an object's inherent tangibility, and musical instruments are particularly tactile objects, benefiting from the further mnemonic of music itself. The core of the article considers Hardy's late poem 'Haunting Fingers: A Phantasy in a Museum of Musical Instruments', which hears instruments speak out their memories of being touched, and through memory feel 'old muscles travel/Over their tense contours'. Revisions to the manuscript show Hardy removing 'death' and privileging instead the immediacy of remembered touch. Paying attention to the reading and note-taking Hardy did within nineteenth-century science, this article traces Hardy's imaginative explorations of the processes involved in playing musical instruments back to discoveries about the workings of the unconscious. Saleeby, James, Maudesley and Bastian informed Hardy's knowledge of the science behind music-playing, while musical haptics helps this study unpack why Hardy attends to the interactions which take place at the point of mechanical contact: finger to key, and to string.